2019
DOI: 10.15402/esj.v4i2.61747
|View full text |Cite
|
Sign up to set email alerts
|

“Community First” for Whom? Reflections on the Possibilities and Challenges of Community-Campus Engagement from the Community Food Sovereignty Hub

Abstract: While community-campus engagement (CCE) has gained prominence in postsecondary institutions, critics have called for a more direct focus on community goals and objectives. In this paper, we explore the possibilities and limitations of community-centred research through our collective experiences with the Community First: Impacts of Community Engagement (CFICE) and the Community Food Sovereignty (CFS) Hub. Drawing on a four-year research project with twelve community-campus partnership projects across Canada, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…As a result, the potential impact of CCE can be significantly diminished and, as some of the CFS partners have noted above, these kinds of evaluations often fail to meaningfully understand CCE impacts and meet community partners' needs. Building on our previous research (Kepkiewicz et al, 2018), we reiterate that CCE is complex and contested and "[we] emphasize the structural limitations of 'community first' CCE, acknowledging that 'community first' CCE is extremely difficult, if not impossible, to achieve within current academic structures"…”
Section: Discussion and Conclusion: Questioning The Impact Of Impactmentioning
confidence: 96%
See 1 more Smart Citation
“…As a result, the potential impact of CCE can be significantly diminished and, as some of the CFS partners have noted above, these kinds of evaluations often fail to meaningfully understand CCE impacts and meet community partners' needs. Building on our previous research (Kepkiewicz et al, 2018), we reiterate that CCE is complex and contested and "[we] emphasize the structural limitations of 'community first' CCE, acknowledging that 'community first' CCE is extremely difficult, if not impossible, to achieve within current academic structures"…”
Section: Discussion and Conclusion: Questioning The Impact Of Impactmentioning
confidence: 96%
“…Beyond the rhetoric of apolitical social change discourse, a growing group of scholars have envisioned CCE as a process that has the potential to challenge inequitable power dynamics, increase community well-being, and encourage systemic change (Kepkiewicz, Levkoe, & Brynne, 2018;Marullo & Edwards, 2000;Mitchell, 2007;Sheridan & Jacobi, 2014;Taylor & Ochocka, 2017). Grain and Lund (2016) suggest this must include incorporating social justice principles into CCE work and ensuring leadership and action emerges directly from community-academic collaborations.…”
Section: Evaluating Cce As Social Changementioning
confidence: 99%
“…Community Food Security/Sovereignty hub Between 2012 and 2016, the Community Food Security/Sovereignty hub of CFICE (hereafter the food hub) supported 12 demonstration projects, all involving community and academic partnerships (Kepkiewicz, Levkoe, & Brynne, 2018) with the aim of advancing more healthy, equitable, and sustainable food systems where the people that produce and harvest food have more decision-making power (Wittman, Desmarais, & Wiebe, 2011).…”
Section: Three Cfice Impact Case Studiesmentioning
confidence: 99%
“…For example, collaborative evaluation of these projects revealed that some partners were more interested in understanding local project successes in terms of immediate social and environmental impacts, while others were more focused on larger issues of process including trust building and transparency among researchers. Still others spoke to a combination of the two (Andrée, Bhatt, et al, 2014;Kepkiewicz et al, 2018). Another tension that emerged was between a focus on local partnerships and those at the regional and national levels through and with Food Secure Canada.…”
Section: Three Cfice Impact Case Studiesmentioning
confidence: 99%
“…matic areas addressing pressing social and ecological issues including violence against women, community food security and food sovereignty (Andrée, Kepkiewicz, Levkoe, Brynne, & Kneen, 2016;Kepkiewicz, Levkoe, & Brynne, 2018;Kepkiewicz, Srivastava, Levkoe, Brynne, & Kneen, 2017;Levkoe et al, 2016;Levkoe, Brem-Wilson, & Anderson, 2019;Levkoe, Erlich, & Archibald, 2019;Nelson & Dodd, 2016), poverty reduction (Erickson, Findlay, & Christopherson-Cote, 2018;Pei, Feltham, Ford, & Schwartz, 2015;Schwartz, Weaver, Pei, & Miller, 2016;Zeng & Honig, 2017), and community environmental sustainability (Martin & Ballamingie, 2016;Nasca, Changfoot, & Hill, 2018). In the second phase of CFICE, from 2015 to 2019, campus and community partners worked on cross-sector collaborations to further develop specific practices and approaches, including community-based CCE brokering (Levkoe, Schembri, & Wilson, 2018;Levkoe & Stack-Cutler, 2018;, student pathways for community impact (Przednowek, Goemans, & Wilson, 2018), and community-based organization access to research tools.…”
mentioning
confidence: 99%